Interaction ritual and the body in a city meat market. Issue 1 (1st January 2020) - Blackledge, Adrian; Creese, Angela
ABSTRACT: Service encounters are often fleeting interactions between strangers, which are beset with trip wires and obstacles. The potential for instability in such encounters is often countered by ritual interaction – small ceremonies in which civility is freely given, and transgression is accounted for and forgiven. Service encounters are not conducted through speech alone, but through embodied communication, in which interactants do not only speak, but point, smile, shrug, nod, gesture, grimace, and so on. In this paper, we consider the deployment of embodied communication, including but not limited to speech, as supportive and remedial interaction in a service encounter between a team of city centre butchers and a customer. The example is from extensive field work conducted in a four-year ethnographic research project across four cities in the UK. The analysis finds that in seeking to understand how people communicate in encounters with strangers, we must pay close attention not only to speech, but also to the ritual deployment of the body as a resource for communication.